Education and knowledge helps combating malaria, but not degedege: a cross-sectional study in Rufiji, Tanzania - Spjeldnæs, Astrid Onarheim (BioMed Central, 2014)
BACKGROUND: Traditional medicine is readily available in Tanzania, and local terms like degedege is widely used for malaria-like illnesses, often associated with supernatural forces. Malaria prevention and intervention efforts can benefit from policy-makers’ awareness of local perceptions and beliefs in the rural areas affected by malaria. This study measured knowledge, attitudes and behaviour towards malaria and malaria-like illnesses. METHODS: A cross-sectional survey was conducted in a rural area in Rufiji, Tanzania. A case report form employing a scoring system was used to capture participants’ knowledge of malaria and another for preventive actions against malaria. Logistic regression was used to assess factors associated with knowledge and preventive action. RESULTS: Most of the participants possessed good knowledge about malaria transmission (82.1%), prevention (85.2%) and where to get treatment (96.4%). Fewer were familiar with fever (58.2%) and other common symptoms of malaria (32.7%), and even fewer actually put their knowledge into action. The action score measured the use of bed net, treatment of nets, indoor use of insecticide residual spraying (IRS), and proportion of households with tight windows, among the participants. As many as 35.7% scored zero on preventive actions, while 37.2% achieved a high action score. Education level and belonging to the age group 30 to 49 were significantly associated with higher knowledge. Education level was associated with higher score for preventive action (OR 2.3, CI 95% 1.2-1.4). Participants generally perceived degedege, a local name for an illness with convulsion, as different from malaria both with regards to cause and possible preventive and curative interventions. CONCLUSION: Respondents considered degedege to have supernatural causes and to need treatment by a traditional healer. This may be one reason for care-seeking shopping and care-seeking delay. Regarding degedege as a separate entity may explain why malaria is not perceived as a serious health problem in the area, and why little preventive actions are taken. While the elders have high status in the society, their lack of knowledge of malaria may impact the care-seeking pattern of their families.